Business gamification for dummies - Duggan, Kris (John Wiley & Sons, 2013)
Gamification is a modern business strategy that leverages principles from games to influence favorable customer behavior on the web in order to improve customer loyalty, engagement, and retention. Gamification can be used by any department in a company (HR, Sales, Marketing, Engineering, Support, etc.), for any web-based experience (mobile, website, retail, community, etc.).